Tracking a decade of food system transformation in Vietnam’s Mekong Delta: Production, consumption, and nutrition - The Ky, Hoang; Ignowski, Elizabeth; Belton, Ben; Huynh, Tuyen; Thanh, Duong Thi; Mai Phuong, Tuan Thi; Son, Nguyen Duy; Mai, Truong Tuyet; TTD, Phuong; Khondker, Murshed-E-Jahan (WorldFish, 2024)
The Mekong River Delta (MRD), Vietnam’s largest food-producing region, faces significant climate-related challenges, including floods, droughts, and salinity from rising sea levels. By utilizing national data from the Vietnam Household Living Standards Survey (VHLSS), Vietnam Statistical Year Book (SYB), and the General Nutrition Survey (GNS), this study examines the changes in food production, consumption patterns, diet, and nutrition status in the MRD of Vietnam from 2010 to 2020. The MRD remains the largest food production region in the country, with households’ production far exceeding their own nutrient needs. However, the region is experiencing declines in in vegetable production, from 465 kg/hh/year (2010) to 206 kg/hh/year (2020). Consequently, household diets in the MRD have shifted to rich animal source foods, sugar- sweetened food and beverage, and FAFH, although the consumption of fish and seafood is the highest in the country. While dietary quality has increased in terms of energy (by 248 kcal/capita/day), protein (up by 12 g/capita/day), and retinol (up by 49 μcg/capita/day), there has been a reduction in calcium (down by 46 mg/capita/day). These dietary transitions have contributed to positive health outcomes for children under five years old, with stunting rates decreasing by 15.8%, underweight rates by 10.1%, wasting by 4.2%, and chronic energy deficiency (CED) in adults by about 7%. However, these changes have also been a factor in the doubling of obesity rates, with adult male obesity reaching 30.1% and female obesity reaching 20.3%. This paper provides strong evidence for helping national and MRD regional policymakers to implement the government's Decree 300 to strengthen local food systems and promote healthy diet patterns in the context of climate change and urbanization.